Effect of Sm2O3 on the physical, structural and optical properties of 40 SiO2 - 40 B2O3 - 10 V2O5 - (10-x) Fe2O3 glasses. (1st May 2023) - Kaur, Jaspreet; Kaur, Paramvir; Mudahar, Isha; Singh, K.
Abstract: The glass composition 40 SiO2 - 40 B2 O3 - 10 V2 O5 - (10-x) Fe2 O3 – (x) Sm2 O3 with x = 0, 2, 4, 6 mol% are prepared using the melt-quench technique. The as-prepared glasses are characterised by different experimental methods such as X-ray diffraction (XRD), Fourier transforms infrared (FTIR) spectroscopy, Raman spectroscopy, UV–visible spectroscopy and vibrating sample magnetometer (VSM) for their structural, optical and magnetic properties. The replacement of Fe2 O3 by Sm2 O3 increases the density of the glasses with decreasing molar volume nonlinearly. Raman, FTIR and XRD spectra indicate that samarium oxide addition increases the glass formation tendency up to 6 mol%. The optical band gap increases with Sm2 O3 concentration and is in the semiconducting range, i.e., 2.2–2.6 eV. The present glasses and glass ceramics can be used as thermoseeds for hyperthermia treatment.